2020
DOI: 10.1159/000508184
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cognitive Impairment and the Role of Demographic Factors in Disease Progression: The Final Results of the Russian Observational Program “DIAMANT”

Abstract: <b><i>Background:</i></b> Chronic cerebral ischemia (CCI) is a form of cerebrovascular disease manifested as a vascular cognitive impairment (VCI). The management of the patients with CCI is determined by a healthy lifestyle and early therapy aimed at correcting and preventing this disease. Divaza is a drug with endothelial protective and nootropic effects. We present the final efficacy and safety analysis of all-Russian, open-label, prospective, observational, multicenter study of Diva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Lactose is an important component of drugs which active pharmaceutical ingredients are obtained by repeated dilution of antibodies. These drugs are effective and safe in the treatment of many diseases [20][21][22][23][24][25][26][27]. Although previous studies already showed the differences between lactose saturated with dilutions of substances from control [3,[6][7][8][9][10], the development of comprehensive methods of quality control of such drugs is still an urgent task.…”
Section: Introductionmentioning
confidence: 99%
“…Lactose is an important component of drugs which active pharmaceutical ingredients are obtained by repeated dilution of antibodies. These drugs are effective and safe in the treatment of many diseases [20][21][22][23][24][25][26][27]. Although previous studies already showed the differences between lactose saturated with dilutions of substances from control [3,[6][7][8][9][10], the development of comprehensive methods of quality control of such drugs is still an urgent task.…”
Section: Introductionmentioning
confidence: 99%